The impact of 1.5-T intraoperative magnetic resonance imaging in pediatric tumor surgery: Safety, utility, and challenges - Becerra, Victoria; Hinojosa, José; Candela, Santiago; Culebras, Diego; Alamar, Mariana; Armero, Georgina; Echaniz, Gastón; Artés, David; Munuera, Josep; Muchart, Jordi (Frontiers in Oncology, 2023)
Objective In this study, we present our experience with 1.5-T high-field intraoperative magnetic resonance imaging (ioMRI) for different neuro-oncological procedures in a pediatric population, and we discuss the safety, utility, and challenges of this intraoperative imaging technology. Methods A pediatric consecutive-case series of neuro-oncological surgeries performed between February 2020 and May 2022 was analyzed from a prospective ioMRI registry. Patients were divided into four groups according to the surgical procedure: intracranial tumors (group 1), intraspinal tumors (group 2), stereotactic biopsy for unresectable tumors (group 3), and catheter placement for cystic tumors (group 4). The goal of surgery, the volume of residual tumor, preoperative and discharge neurological status, and postoperative complications related to ioMRI were evaluated. Results A total of 146 procedures with ioMRI were performed during this period. Of these, 62 were oncology surgeries: 45 in group 1, two in group 2, 10 in group 3, and five in group 4. The mean age of our patients was 8.91 years, with the youngest being 12 months. ioMRI identified residual tumors and prompted further resection in 14% of the cases. The mean time for intraoperative image processing was 54 ± 6 min. There were no intra- or postoperative security incidents related to the use of ioMRI. The reoperation rate in the early postoperative period was 0%. Conclusion ioMRI in pediatric neuro-oncology surgery is a safe and reliable tool. Its routine use maximized the extent of tumor resection and did not result in increased neurological deficits or complications in our series. The main limitations included the need for strict safety protocols in a highly complex surgical environment as well as the inherent limitations on certain patient positions with available MR-compatible headrests.